2016
DOI: 10.1097/md.0000000000005088
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function changes and its influencing factors after preoperative brace treatment in patients with adolescent idiopathic scoliosis

Abstract: Background:The aim of the study was to retrospectively investigate the changes in pulmonary function and its influencing factors in patients with adolescent idiopathic scoliosis (AIS) undergoing preoperative brace treatment or not.Methods:Total 237 AIS patients (43 boys, 194 girls) who underwent operations and had a complete record of pulmonary function tests were enrolled and were divided into preoperative brace treatment group (brace treatment group, n = 60) and without preoperative brace treatment group (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…22 But the effects of bracing on respiratory mechanics may vary according to curve magnitude, brace design, restrictive effects on rib cage and trunk mobility, applied corrective forces, how long the brace is worn, and so on. 4,8 In this study, the unbraced and braced condition comparisons have shown that there was a mild decrease (defined by the American Thoracic Society) 23 in FEV 1 (with mean change 18.8%), VC (with mean change 12.4%), FVC (with mean change 18.4%), MVV (with mean change 11.7%), and PEF (with mean change 18.4%) values of spirometric measurements while wearing a brace when compared with the unbraced condition. These alterations may be due to the correcting forces exerted by the brace and its possible limiting effect on the expansion of the rib cage during inspiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 But the effects of bracing on respiratory mechanics may vary according to curve magnitude, brace design, restrictive effects on rib cage and trunk mobility, applied corrective forces, how long the brace is worn, and so on. 4,8 In this study, the unbraced and braced condition comparisons have shown that there was a mild decrease (defined by the American Thoracic Society) 23 in FEV 1 (with mean change 18.8%), VC (with mean change 12.4%), FVC (with mean change 18.4%), MVV (with mean change 11.7%), and PEF (with mean change 18.4%) values of spirometric measurements while wearing a brace when compared with the unbraced condition. These alterations may be due to the correcting forces exerted by the brace and its possible limiting effect on the expansion of the rib cage during inspiration.…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, the effects of bracing on thorax mechanics, chest mobility, and pulmonary functions are considered inevitable. 4 Bracing has important positive effects on scoliosis treatment in the long term, such as reducing curve magnitude and rib hump, and improving cosmetic appearance and trunk symmetry. 5,6 However, wearing a brace for many years can be a traumatic experience for adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scientific literature is in agreement that with appropriate indications-still-growing and well-documented progressive curves between 20 • and 45 • -a well-designed and adapted brace can provide a correction of 50%, which can stop the curve's progression in most cases [8]. However, the effects of bracing on thorax mechanics, chest mobility, and pulmonary functions are considered inevitable [11]. Other conservative methods, based on exercise approaches, such as Schroth exercises [12], or Global Postural Reeducation (GPR) [13], may be beneficial and appear to cause fewer adverse effects because they allow the patient to move without restriction.…”
Section: Introductionmentioning
confidence: 67%
“…These braces are prescribed by physicians to patients and by wearing them, after a while, the structure and shape of the spinal cord are reversed. [9][10][11] Today, researchers are reviewing a variety of brace models so that, by designing and analyzing a variety of braces, they are planning to present the best and most recent models for scoliosis patients. [12][13][14] This study has been designed to simulate and compare braces composed of three different materials to determine the optimal material.…”
mentioning
confidence: 99%